The written suburb : an American site, an ethnographic dilemma - Dorst, John Darwin (Contemporary ethnography series., 1989)
Chadds Ford, an upscale suburb in southeastern Pennsylvania, devotes a lot of energy to creating a historical identity. Numerous institutions participate in this task, including museums, a land conservancy dedicated to the preservation of its historical landscape, and the Historical Society, which is responsible for an annual community celebration. Larger institutions related to regional tourism and suburban development generate a steady flow of texts about Chadds Ford in the form of glossy travel magazines, pamphlets, brochures, and gallery displays.